Transcriptional and epigenetic dynamics of sex determining gene PdFERR and MADS-box related genes during flower development in Populus deltoides - He, Yu-Jie; Chen, Cong; Guo, Ying; Tang, Jian; He, Jie; Mei, Li-Na; El-Kassaby, Yousry A.; Wu, Huaitong; Yin, Tongming; Xue, Liang-Jiao (Frontiers in Plant Science, 2025)
Manipulation of genes controlling sex differentiation, flower development, and flowering in poplar is pivotal to shortening the juvenile phase for a speed breeding system or eliminate flowering to reduce the dispersions of polluting pollens and hairy seeds. The sex-determining gene (PtARR17/PdFERR) and some core transcriptional regulators, such as the MADS-box gene AGMOUS, have been identified in Populus. However, the interactions among them have not been explored well. Here, we integrated RNA-seq, small RNA-seq, and Bisulfite-seq to characterize the dynamics of regulatory genes at multiple levels. Ninety-six MADS-box genes were identified, which can be grouped into 6 clusters based on expression level. The E-class genes exhibited diverse expression patterns, suggesting differentiated regulatory roles. Through deep sequencing, 236 miRNAs targeting more than 4500 genes were annotated. Eight MADS-box genes were predicted as direct targets of miRNAs. At the genome level, DNA methylation at stage T2 is higher than in the later stages. More than 10K genes were differentially methylated between female and male flower buds, indicating the significant regulatory roles of DNA methylation in flower differentiation. The MADS-box-centered regulatory network consists of co-expressed transcription factors, and miRNA genes were constructed. The correlations between PdFERR and transcription factors, including MADS-box genes and other environment-responsive genes, provide clues to understand the labile sex expression. Our study provides candidate genes for engineering of flower development process for trait improvement.